Surgical anatomy of double pyramidal lobe on total thyroidectomy: a rare case report. - Kaklamanos, Ioannis; Zarokosta, Maria; Flessas, Ioannis; Zoulamoglou, Menelaos; Katsoulas, Theodoros; Birbas, Konstantinos; Troupis, Theodoros; Mariolis-Sapsakos, Theodoros (J Surg Case Rep, 2017)
Double pyramidal lobe is a scarce anatomical variation of the thyroid gland. Its presence impinges on the completeness of total and subtotal thyroidectomy and the postoperative treatment. Surgeons should be always aware of this variation in order to perform sufficient resection of the thyroid gland and minimize the possibility of recurrence of benign and malignant thyroidopathies.